The Prognostic Value of Prolonged QTc Interval and Tp-Te/QT Index at Admission in Patient with Acute Myocardial Infarction - سعيد, سعيد; أكرم جحجاح; باسم معروف (Latakia University Journal -Medical Sciences Series, 2023)
Background:Syria is one of the countries with a high risk of ischemic heart disease. It is one of the most causes of morbidity and mortality worldwide. In this research, we will study the prognostic value of prolonged QTc and TpTe/QTc index at admission in patient with myocardial infarction. Methods and Material:The study sample included 103 patients diagnosed with acute myocardial infarction with or without ST-segment elevation.76 patients with a QTc˂443 ms and 27 patients with a QTc≥443ms. 90 patients with a TpTe/QT˂0.3 and 13 patients with TpTe/QT≥0.3. Results:Prolongation of QTc at admission was associated with high rates of major cardiac compliations such as cardiogenic shock(P value=0.0001) and arrhythmias (P value=0.0001) and cva(P value=0.03) and the prolongation of QTc was associated with increased length of hospital stay(P value=0.004) and an increased death rate (P value=0.0001). Prolongation of TpTe/QT Index at admission was associated with high rates of major cardiac complitation such as cardiogenic shock( P value=0.0001) and arrhythmias (P value=0.0001) and cva(P value=0.005) and the prolongation of QTc was associated with increased length of stay(P value=0.02) and an increased death rates(P value=0.0001).